2017
DOI: 10.1007/s00276-017-1857-4
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries of the thoracic paravertebral space: potential risks and benefits of the thoracic paravertebral block from an anatomical perspective

Abstract: PurposeThoracic paravertebral block (TPVB) may be an alternative to thoracic epidural analgesia. A detailed knowledge of the anatomy of the TPV-space (TPVS), content and adnexa is essential in understanding the clinical consequences of TPVB. The exploration of the posterior TPVS accessibility in this study allows (1) determination of the anatomical boundaries, content and adnexa, (2) description of an ultrasound-guided spread of low and high viscous liquid.MethodsIn two formalin-fixed specimens, stratification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
(43 reference statements)
3
28
1
1
Order By: Relevance
“…Recently, the boundaries of the TPV space have been studied in human medicine. These boundaries were the internal IIM and superior costotransverse ligament on the posterior side, the parietal PL and the endothoracic fascia in the anterolateral side and the vertebral body, intervertebral disk, and foramen in the medial side (Bouman et al, 2017). The pattern of distribution observed in our study was consistent with these findings, where the separation of the TPV space in a subendothoracic and extrapleural compartment was not observed and the TPV space had a lateral communication with the intercostal space.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, the boundaries of the TPV space have been studied in human medicine. These boundaries were the internal IIM and superior costotransverse ligament on the posterior side, the parietal PL and the endothoracic fascia in the anterolateral side and the vertebral body, intervertebral disk, and foramen in the medial side (Bouman et al, 2017). The pattern of distribution observed in our study was consistent with these findings, where the separation of the TPV space in a subendothoracic and extrapleural compartment was not observed and the TPV space had a lateral communication with the intercostal space.…”
Section: Discussionsupporting
confidence: 89%
“…None of the previous studies observed the lumbar spread of the injected solution (Monticelli et al, 2017;Portela et al, 2017;Ferreira et al, 2018). Despite this, there are previous reports attributing the origin of the psoas muscle as the caudal boundary of the TPV space in humans (Lönnqvist and Hildingsson, 1992), and recently Bouman et al (2017) showed a spread of dye into the lumbar paravertebral space. In our study, 42% of the injections within the TPV space (5/12) were distributed beyond the psoas muscle origin, reaching lumbar regions.…”
Section: Discussionmentioning
confidence: 89%
“…Several ultrasound-guided techniques have been developed since 2009 [8][9][10][11] and although the basic procedure is still widely used [12], these ultrasound-guided techniques are now being used more frequently. The thoracic paravertebral space includes the thoracic spinal nerves, which emerge from the medial side of this space as they exit the thoracic intervertebral foramen [13]. The thoracic paravertebral space is triangular in transverse section with the medial base formed by the posterolateral aspect of the vertebral body, articular process, and intervertebral foramen [7,13,14].…”
Section: Clinical Background and Anatomymentioning
confidence: 99%
“…The thoracic paravertebral space includes the thoracic spinal nerves, which emerge from the medial side of this space as they exit the thoracic intervertebral foramen [13]. The thoracic paravertebral space is triangular in transverse section with the medial base formed by the posterolateral aspect of the vertebral body, articular process, and intervertebral foramen [7,13,14]. The anterolateral border is formed by the parietal pleura; and the posterior border is formed by the transverse process, heads of ribs, and superior costotransverse ligament [7,13,14].…”
Section: Clinical Background and Anatomymentioning
confidence: 99%
See 1 more Smart Citation